Marketing Communication Plan of Mega Star Event Planner Innovation to Survive During and Post-Pandemic - Osin Mega Bintang (COMMENTATE: Journal of Communication Management, 2022)
The pandemic situation that has been ongoing from March 2020 to 2021 has plunged the event industry. This is also felt by the Mega Star Event Planner business that offers event planning services. The right strategy is needed to survive and sustain its business during and after a pandemic. Therefore, the Mega Star Event Planner will innovate by developing their product, which is to create an event package with the COVID-19 protocol starting from swab tests and strict procedure in physical distancing. This marketing communication plan that was created to market the results of this innovation was made using the SOSTAC method developed by PR Smith. This plan is entitled Marketing Communication Plan of the Mega Star Event Planner Innovation Results with the aim of Mega Star Event Planner business surviving during and after the pandemic.